Indlæring af fagtekstproduktion på fremmedsprog: om fagordbøger som prædeterminerede læringsværktøjer - Leroyer, Patrick; Køhler Simonsen, Henrik (LexicoNordica, 2018)
This article discusses the role of specialized dictionaries for foreign-language text production in learning situations. First, we carried out a controlled experiment with ten test subjects. The test subjects were asked to produce a LinkedIn sales text and the experi- ment generated a total of ten screen recordings, ten texts, ten self- assessments and ten rubric feedback sheets. Second, we analyzed the data and found that specialized dictionaries are not, as one would normally expect, used by students to communicate, but to learn how to communicate.